Pemanfaatan Aplikasi Canva Sebagai Media Pembelajaran Sosiologi dalam Meningkatkan Motivasi Belajar dan Kreativitas Siswa Kelas X SMA Negeri 1 Sidareja - Waryatin (UM Purwokerto Press, 2024)
The utilization of technology in Sociology learning can be used as a learning support, especially in schools that have implemented an independent curriculum. Learning media is not only a tool for presenting scientific information but also as a tool to help interact to achieve good learning outcomes. One of the technology-based learning media is the application, of the many applications that exist in the world of technology is the Canva application. Teachers can provide opportunities for students to engage their abilities and motivation in learning materials through Canva applications. This research was conducted using a qualitative research approach using observation, interview, documentation, and questionnaire techniques. The purpose of this study was to determine how the use of Canva application as a Sociology learning media in increasing learning motivation and creativity of class X students of SMA Negeri 1 Sidareja in the even semester of the 2023/2024 academic year. The results of this study indicate that Canva-based learning media is very well used in the Sociology learning process because it can increase students' enthusiasm and motivation in participating in Sociology learning. The Canva application can also increase student creativity in making Sociology material designs, such as poster and infographic designs. Canva-based learning media can also increase student creativity, especially in making designs, so that learning becomes more fun.